1999
DOI: 10.1128/jb.181.5.1694-1697.1999
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Expression of the Minor Pilin Subunit, CooD, Determines the Number of CS1 Pili Assembled on the Cell Surface of Escherichia coli

Abstract: CooD, the minor subunit of CS1 pili of enterotoxigenicEscherichia coli, is essential for the assembly of stable, functional pili. We previously proposed that CooD is a rate-limiting initiator of CS1 pilus assembly and predicted that the level of CooD expression should therefore determine the number of CS1 pili assembled on the cell surface. In this study, we confirm that CooD is required for the initiation of pilus assembly rather than for the stabilization of pili after they are assembled by demonstrating tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Using the same in vitro adhesion model, we have shown here that particles adsorbed with dscCfaE but not dscCfaB induce MRHA of human and bovine red cells. Our demonstration that dsc19CfaE/R181A(His)6 failed to agglutinate human or bovine erythrocytes substantiates the findings of Sakellaris et al (1999b) and suggests that this fully conserved, charged residue sits in the ligand-binding pocket of CfaE and related Class 5 adhesins and plays a direct role in binding. Moreover, we found that anti-CfaE serum is superior to anti-CFA/I and anti-CfaB sera with respect to inhibiting MRHA induced by CF-homologous ETEC and was also more broadly inhibitory against ETEC that express other fimbriae of the same subclass.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Using the same in vitro adhesion model, we have shown here that particles adsorbed with dscCfaE but not dscCfaB induce MRHA of human and bovine red cells. Our demonstration that dsc19CfaE/R181A(His)6 failed to agglutinate human or bovine erythrocytes substantiates the findings of Sakellaris et al (1999b) and suggests that this fully conserved, charged residue sits in the ligand-binding pocket of CfaE and related Class 5 adhesins and plays a direct role in binding. Moreover, we found that anti-CfaE serum is superior to anti-CFA/I and anti-CfaB sera with respect to inhibiting MRHA induced by CF-homologous ETEC and was also more broadly inhibitory against ETEC that express other fimbriae of the same subclass.…”
Section: Discussionsupporting
confidence: 83%
“…Before recognition of a CFA/I minor structural subunit, Buhler et al asserted that CFA/I consisted of a CfaB homopolymer, and showed that monomeric CfaB made by boiling CFA/I fimbriae inhibited MRHA triggered by purified CFA/I or CFA/I-ETEC (Buhler et al, 1991). In a methodical molecular analysis of another Class 5 adhesive fimbria CS1, Scott et al identified the minor structural subunit CooD and showed that it was required to initiate fimbrial assembly (Froehlich et al, 1994;Sakellaris et al, 1996;1999b). Sakellaris et al identified Arg-181 of CooD (and the corresponding residue in CfaE) as one residue whose alanine replacement mutant produced fimbriae but abolished MRHA of E. coli when complemented with a plasmid harbouring the other required bioassembly genes (cooBAC) (Sakellaris et al, 1999b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CS1 consists of hundreds of major CooA subunits [Galkin et al, 2013]: a periplasmic chaperone protein (CooB), an outer membrane protein (CooC), and a tip protein (CooD) [Voegele et al, 1997]. Previous studies have shown that expression of the tip protein of CS1 is required for the initiation of fimbrial assembly and adhesion [Sakellaris et al, 1999b]. Unlike other colonization factors, the CS2 operon has been found on the ETEC chromosome [Perez-Casal et al, 1990].…”
Section: Introductionmentioning
confidence: 99%
“…Colonization factor antigen I (CFA/I) was the first such adhesive fimbria to be discovered and is the archetype of eight class 5 ETEC fimbriae (Evans et al, 1978;Anantha et al, 2004). Of the other seven class 5 fimbriae, CS1 fimbriae have been extensively studied, particularly their biogenesis and regulation (Sakellaris et al, 1996(Sakellaris et al, , 1999Munson et al, 2002). Like CS1, CFA/I is encoded by a four-gene operon and is assembled by the alternate chaperone pathway, which has been distinguished from the classic chaperone-usher pathway that guides the assembly of class I pili such as type 1 and P pili (Soto & Hultgren, 1999;Anantha et al, 2004).…”
Section: Introductionmentioning
confidence: 99%